Inovasi Sribumi Dalam Partisipasi Kompetisi Inovasi Kota Palembang Tahun 2024 - Rahman, M Arief; Prayoga, Ade Dwi (Fakultas Teknik Universitas Palangka Raya, 2024)
The Palembang City Innovation Competition 2024 is a strategic event to encourage community innovation in supporting sustainable city development. One of the featured innovations in this competition is “Sribumi” (Sriwijaya Berbudaya dan Memelihara), which combines local cultural preservation, environmental management, and the application of modern technology. This innovation focuses on strengthening Palembang City's cultural identity while addressing environmental challenges through a community-based approach. The competition process involved selection stages, participant mentoring, and evaluation by an independent panel of judges. As the first winner of the Thematic Community category, “Sribumi” demonstrated positive impacts through cross-sector collaboration and active community participation. The results of this competition not only provide tangible benefits for Palembang City but also reflect the importance of synergy between culture, environment, and technological innovation. This activity can be a reference for Palembang city and other cities in encouraging an inclusive and sustainable innovation ecosystem.